Hypertrophic Cardiomyopathy and Sports - Maznev, Ivan; Dimitrova, Antoaneta (European Scientific Journal, ESJ, 2018)
Hypertrophic cardiomyopathy (HCM) is one of the most common causes of sudden cardiac death (SCD) in athletes. Knowledge of the problem is essential for detection of the disease. According to the current recommendations of the European Society of Cardiology (ESC), in individuals with established HCM disease, including those without phenotypic expression, participation in competitive sports is forbidden. The recommendations of the American College of Cardiology/American Heart Association (ACC/AHA) are more liberal, allowing participation in competitive sports in people with non-phenotypic manifestations of the disease and participation in low-intensity sports for patients with phenotypic manifestation. An individual approach will most likely be adopted in the future, mainly on the basis of precise risk stratification.